Evaluation of GeneXpert for Quantification Viral Load Hepatitis C Virus - Chyntia Olivia Maurine Jasirwan; Irsan Hasan; Andri Sanityoso Sulaiman; Rino Alvani Gani (The Indonesian Society for Digestive Endoscopy, 2020)
Background: GeneXpert has been used for Mycobacterium tuberculosis testing, but is currently available for HCV RNA testing. GeneXpert assay is expected to be more accurate, efficient, and cost-effective for HCV viral load quantification. This study intended to evaluate the new method quantification of plasma HCV RNA by the GeneXpert in comparison to the Roche Cobas TaqMan 96 as standard diagnostic tools.Method: A total of 54 HCV-infected plasma samples with anti-HCV positive were examined by GeneXpert assay, followed with Cobas TaqMan 96 for quantification of HCV RNA. Correlation was performed by Pearson test (in log10) and diagnostic test by Chi-square test. Sensitivity and specificity of the GeneXpert assay measured by calculating 2x2 contingency table. Bland-Altman plot were generated to assess the mean difference between the two assays.Results: GeneXpert has strong correlation to the Roche Cobas TaqMan 96 (R=0.993; P value 0.001). GeneXpert has sensitivity of 100% (95% CI: 90–100%) and specificity of 90% (95% CI: 54.1–99.5%). The Bland Altmand plot showed that one sampel has 1 log difference with the Roche Cobas TaqMan 96 measurement result.Conclusion: There was a strong correlation in the measurement of HCV RNA by GeneXpert and moreover its assay also has an excellent overall performance compared to Cobas TaqMan 96. Thus, it can be considered as a reliable tools for HCV virological response monitoring.